Exploring Suicide Methods in Sudan: Insights from General Hospitals - Khalid Abdallah Abdalhai; Abdelghani Elsheikh Abdelghani; Mohamed Hassan Ahmed; Isra Balla Babiker (Pan-African Journal of Health and Environmental Science, 2024)
Background: Suicide is a major concern worldwide. Understanding the various methods and tools used for suicide is crucial for developing effective preventive strategies. The objective of this study is to investigate and assess methods of suicide in Sudan.